Economic Value Added Dan Market Value Added Serta Perilaku Harga Saham Perusahaan Yang Listing Di Jakarta Islamic Index (Periode 2010-2014) - Khairuriza Khairuriza; Leo Herlambang (Universitas Airlangga, 2016)
Stern Stewart & Co. introduced new methods of measuring financial performance based on the added value produced by the company, these methods being Economic Value Added (EVA) and Market Value Added (MVA). The purpose of this research is to analyze the effect of EVA and MVA toward the stock price of companies listed in Jakarta Islamic Index (JII) for the year period 2010-2014.The data used in this research are secondary data comprising of yearly data for the period 2010-2014. The analysis employed in this research is through using multiple linear regression analysis with α of 0.05.The research suggest that EVA and MVA partially and simultaneously have significance effect towards the stock price of the company enlisted in JII. With α of 0.162 or 16.2%, this shows that 16, 2% of stock price in JII is affected by EVA and MVA, whereas 83, 8% is affected by other variables.